HUBUNGAN TERAPI MINDFULNESS TERHADAP REGULASI DIRI REMAJA DENGAN MASALAH MENTAL EMOSIONAL DI KLINIK TALENTA CENTER - Kayla Sekardita (2022)
Adolescence is a period of transition from children to adults. During adolescence, a person is faced with various kinds of problems, such as physical, social, mental, and emotional changes. Adolescent emotional development usually has great energy, while self-regulation is not perfect. Therefore, adolescents are prone to decreased self-regulation, and causes mental emotional problems such as anxiety, depression, sleep disturbances, to the idea of hurting yourself. Mindfulness therapy helps individuals learn to observe thoughts, emotions and events that occur. This study aims to determine the relationship between mindfulness therapy and self-regulation in adolescents with mental emotional problems. Data collection used purposive sampling method on 30 patients at the Talenta Center Clinic who met the criteria. This type of research is quantitative with analytical observational research with cross sectional design. The results of the correlation test on the variables of mindfulness and self-regulation showed a value of 0.848, it can be concluded that there is a strong relationship between mindfulness therapy on adolescent self-regulation with mental emotional problems